Find an expression which represents the difference when (6x-3y) is subtracted from (9x+2y) in simplest terms.
1 answer:
Answer:
![3x+5y](https://tex.z-dn.net/?f=3x%2B5y)
Step-by-step explanation:
Subtract (6x-3y) from (9x+2y):
![(9x+2y)-(6x-3y)](https://tex.z-dn.net/?f=%289x%2B2y%29-%286x-3y%29)
This can also be seen as:
![(9x+2y)-1(6x-3y)](https://tex.z-dn.net/?f=%289x%2B2y%29-1%286x-3y%29)
Distribute the -1 to (6x-3y):
![(9x+2y)-1(6x)-1(-3y)\\\\(9x+2y)-6x+3y](https://tex.z-dn.net/?f=%289x%2B2y%29-1%286x%29-1%28-3y%29%5C%5C%5C%5C%289x%2B2y%29-6x%2B3y)
Simplify the parentheses:
![9x+2y-6x+3y](https://tex.z-dn.net/?f=9x%2B2y-6x%2B3y)
Group like terms:
![(9x-6x)+(2y+3y)](https://tex.z-dn.net/?f=%289x-6x%29%2B%282y%2B3y%29)
Combine:
![3x+5y](https://tex.z-dn.net/?f=3x%2B5y)
This expression can't be further simplified. Therefore, 3x+5y is the answer.
:Done
You might be interested in
I believe the answer is 4
Sorry I can’t answer this right now but I’ll will answer later
Answer:
75%
Step-by-step explanation:
It's right
Answer:
Step-by-step explanation:
y + 4 = -6(x - 7)
y + 4 = -6x + 42
y = -6x + 38
Answer:
180
Step-by-step explanation:
for two angles to be supplementary, their sum must be equal to 180°